2014
DOI: 10.1130/g35991.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal, long-term, and short-term deformation in the Central Range of Taiwan induced by landslides

Abstract: Seasonal movement of GPS stations is often attributed to hydrological loading and other environmental factors. For the first time we observe seasonal motion associated with slow-moving landslides. Eight of 26 continuous GPS (cGPS) sites in the Central Range of Taiwan show long-term landslide-induced motion at rates of ~3-15 mm/yr, ~20%-60% of their tectonic interseismic velocities. The directions of movements after heavy rains and in the wet season are consistent with the slope directions derived from a high-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…For K = 9, a single station in the mountain range is isolated as a cluster (Figure S1h, labeled as LC, black). The data might be contaminated by local and seasonal effects such as landslides due to the heavy rainfall (e.g., Hsu et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…For K = 9, a single station in the mountain range is isolated as a cluster (Figure S1h, labeled as LC, black). The data might be contaminated by local and seasonal effects such as landslides due to the heavy rainfall (e.g., Hsu et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, the study of slow-moving landslides may lead a better understanding of the physical processes governing both slow and rapid landslides (Palmer, 2017). In recent years, various studies of slow-moving landslides (e.g., Bennett et al, 2016;Handwerger et al, 2013Handwerger et al, , 2015Hsu et al, 2014;Iverson & Major, 1987;Lacroix et al, 2014Lacroix et al, , 2015Reid, 1994;Schulz et al, 2009;Zerathe et al, 2016) have revealed a rich diversity in kinematics, with various forcing factors, for example, rainfall, earthquakes, glacial retreat, and anthropogenic activity. These forcings act over a wide variety of timescales, from seconds (earthquakes Lacroix et al, 2014) to several decades (glacial retreat Strozzi et al, 2010), thus making their study challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Landslide motion is often interpreted to occur as a direct consequence of external forcing factors (e.g., Handwerger et al, 2013Handwerger et al, , 2015Hsu et al, 2014;Lacroix et al, 2014;Reid, 1994;Zerathe et al, 2016), such as rainfall or ground shaking (i.e., from earthquakes). However, different internal processes may also influence landslide motion; for example, progressive failure is thought to play a key role in the initiation of landslide motion (Amitrano, 2004;Carey & Petley, 2014;Eberhardt et al, 2004;Gischig et al, 2016;Lacroix & Amitrano, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We select 267 CGPS stations that have continuously recorded more than 5 years of data and with data covered more than 70% of a year. We do not include stations located near areas subject to seasonal slow-moving landslide area in the Central Range (Hsu et al, 2014).…”
Section: Continuous Gps Measurementsmentioning
confidence: 99%